Efficacy and Safety of Psilocybin-Assisted Therapy for Depression: A Meta-Analysis of Randomised Controlled Trials - Siti Nashria Rusdhy; Andrian Fajar Kusumadewi; Carla Raymondalexas Marchira; Mustika Suci Mahardikaningrum; Teresa Lalita Wiryarini; Devira Ayu Wulandari (Open Access Indonesian Journal of Medical Reviews, 2026)
Psilocybin-assisted therapy shows promise for depression, though current evidence relies on Phase 2 trials with notable methodological limitations. We conducted a systematic review and meta-analysis of randomized controlled trials (RCTs) evaluating psilocybin-assisted therapy for major or treatment-resistant depression up to February 2024. We evaluated depressive symptom severity using random-effects meta-analysis, moderator analyses, Cochrane Risk of Bias 2, and GRADE methodology. Nine RCTs (N=514) were included. Psilocybin therapy demonstrated a large pooled effect size for symptom reduction (SMD = 1.270, 95% CI: 0.865–1.676, p<0.001). However, substantial heterogeneity was observed (I² = 79.1%). Comparator type significantly moderated outcomes, with waitlist controls showing substantially larger effects than active/placebo controls. Overall GRADE certainty of evidence was rated LOW due to risk of bias, heterogeneity, short-term outcomes, and publication bias concerns. In conclusion, while psilocybin-assisted therapy yields a large pooled effect estimate for depression, current findings are preliminary. Results are heavily qualified by methodological constraints, including waitlist-inflated efficacy, compromised blinding from subjective psychedelic effects, and the confounding influence of integrated psychological support. Confirmation through robust Phase 3 trials is required before supporting routine clinical implementation.